Effects of dimethyl sulfoxide in cholesterol-containing lipid membranes: A comparative study of experiments in silico and with cells - de Ménorval, M.-A. (2012)
Dimethyl sulfoxide (DMSO) has been known to enhance cell membrane permeability of drugs or DNA. Molecular dynamics (MD) simulations with single-component lipid bilayers predicted the existence of three regimes of action of DMSO: membrane loosening, pore formation and bilayer collapse. We show here that these modes of action are also reproduced in the presence of cholesterol in the bilayer, and we provide a description at the atomic detail of the DMSO-mediated process of pore formation in cholesterol-containing lipid membranes. We also successfully explore the applicability of DMSO to promote plasma membrane permeability to water, calcium ions (Ca2+) and Yo-Pro-1 iodide (Yo-Pro-1) in living cell membranes. The experimental results on cells in culture can be easily explained according to the three expected regimes: in the presence of low doses of DMSO, the membrane of the cells exhibits undulations but no permeability increase can be detected, while at intermediate DMSO concentrations cells are permeabilized to water and calcium but not to larger molecules as Yo-Pro-1. These two behaviors can be associated to the MD-predicted consequences of the effects of the DMSO at low and intermediate DMSO concentrations. At larger DMSO concentrations, permeabilization is larger, as even Yo-Pro-1 can enter the cells as predicted by the DMSO-induced membrane-destructuring effects described in the MD simulations. © 2012 de Ménorval et al.